Alcohol brands' use of age-restriction controls on Facebook and Instagram in Australia - Hannah Pierce; Abbie-Clare Vidler; Julia Stafford; Danica Keric (Sax Institute, 2022)
Objectives: Since 2017, the self-regulatory alcohol advertising system in Australia has required alcohol marketers to activate age-restriction controls on social networking sites to prevent access to children. With no monitoring mechanisms, the level of compliance with this requirement is unknown. We aimed to identify the extent to which the dominant alcohol companies in Australia have activated age-restriction controls on their official brand accounts on Facebook and Instagram. Study type: Nonexperimental descriptive study. Methods: We identified the brands owned by the top three beer, wine and spirit companies by market share in Australia, and located their official Facebook and Instagram accounts. International accounts were used when Australia-specific accounts did not exist. Two researchers independently attempted to access all accounts on a computer by entering the URL into a web browser that was not logged into either platform. We recorded the accessibility and audience size of each account. Results: For the 195 alcohol brands that were available for sale in Australia through the nine top companies, we identified 153 Facebook accounts (84 Australian, 69 international) and 151 Instagram accounts (77 Australian, 74 international). We found 28% of Instagram and 5% of Facebook accounts did not have age-restriction controls activated. Similar proportions of Australian and international accounts on both platforms were not using controls. Only two companies were compliant across all of their accounts. Conclusions: Compliance with the industry marketing code requirement for age-restriction controls is inconsistent among the largest alcohol companies operating in Australia. The industry-managed regulatory system is not preventing children's access to alcohol content on social networking sites.